Estudo da função ventricular pela técnica do speckle tracking strain em pacientes críticos com sepse: potenciais implicações prognosticas - Mariana de Braga Lima Carvalho Canesso (2018)
In the intensive care setting, cases sepsis are the main causes of mortality. Therefore, it is important to identify tools that are accurate and reliable in assessing the severity of the infection and the patient's prognosis. The speckle tracking echocardiography (STE) represents a marker of early ventricular dysfunction with potential value in risk stratification and clinical management of patients. Preliminary data concerning the utility of STE as a marker of myocardial dysfunction in patients with sepsis are promising. We hypothesize that the STE technique can predict response to therapy and in-hospital outcome. The aim of this study was to evaluate STE in patients with sepsis admitted to an intensive care unit (ICU), comparing values of myocardial strain at inclusion with values obtained after 7 days of treatment and determining the potential prognostic value of STE. We conducted a cohort prospective observational study in the ICU of the University Hospital of the Federal University of Minas Gerais (HC-UFMG). Our study included all adult patients (≥ 18 years of age) with sepsis or septic shock, initiated within 24 hours of hospital admission, without cardiomyopathy or insufficient image quality for STE. We collected clinical and laboratory data and performed echocardiographic studies on days 1 and 7 post study inclusion. These patients were accompanied until hospital discharge or death. We initially selected 56 patients and 26 patients were included in the final analysis of this study. Median age was 57.0 [35.8/64.8] years, and 54% were female. Septic shock was diagnosed in 88%. The baseline APACHE II and SOFA score were 15 [12.8/21.5] and 8 [5.8/11.3], respectively. The left ventricular (LV) ejection fraction at baseline was 65.6 ± 9.1%, without changes during treatment. Despite the preserved LV ejection fraction, the mean absolute value of left ventricular myocardial strain was reduced in six patients (23%) at inclusion, considering the lower reference value of -17%. During hospital stay, seven patients died. LV and RV longitudinal strain increased significantly in the patients who survived (-18.8 ± 3.6 at D1 vs -20.8 ± 2.5 at D7; p = 0.003; and -21.3 ± 4.9 at D1 vs -24.3 ± 5.8 at D7; p = 0.035, respectively), whereas strain values remained unchanged in those who died. After adjustment for the SOFA score, RV longitudinal strain at admission was associated with in-hospital mortality (adjusted odds ratio [OR] 0.760; 95% confidence interval [CI] 0.591 – 0.977; p - 0.033). In conclusion, these results demonstrated that STE improved significantly after the first week of treatment in patients with sepsis who survived compared with those patients who died during hospitalization. RV strain at admission predicted in-hospital mortality. An improvement in STE during sepsis treatment appears to be a useful tool for predicting in-hospital outcome.